Pengaruh Tarif Pajak Pertambahan Nilai Dan Literasi Pajak Terhadap Perilaku Komsumtif Pada Generasi Z - Muhammad Faiq Irfansyah; Linawati Linawati; Erliana Erliana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of value-added tax rates and tax literacy on consumptive behavior in generation Z. This study uses primary data by distributing questionnaires to 100 students of the Applied Bachelor of Tax Accounting Study Program at Pamulang University. The research sample was determined using the purposive sampling method. The data analysis techniques used were descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis tests assisted by using IBM SPSS statistical 30 software. The results of this study show that (1) the value-added tax rate partially affects the consumptive behavior in the generation of 0.001 with a t calculation of 3.316. (2) Tax literacy has a profound effect on consumptive behavior in generation Z of 0.001 with a t calculation of 6.021. (3) Value-added tax rate and tax literacy simultaneously affect the consumptive behavior of generation Z by 0.001 with an F calculation of 55.438.